Gene Order of the Poliovirus Capsid Proteins - Rekosh, David (1972)
Two methods were used to determine the genetic map of the poliovirus capsid proteins. The first method uses pactamycin, a drug which selectively inhibits the initiation of protein synthesis and causes a change in the relative amounts of capsid proteins synthesized. This differential effect on each of the capsid proteins is interpreted as indicating the relative distance of each protein from the initiation site of protein synthesis. The second method involves an analysis of coat precursor molecules released from polyribosomes after a series of short pulses of different length terminated by addition of emetine, a drug which stops all protein synthesis almost immediately after its addition. As the pulse length is increased, each of the capsid proteins within the precursor gains radioactivity with different kinetics. From these kinetics, it is possible to determine the gene order of the capsid proteins within the precursor as well as a rate of protein synthesis. Both methods indicate a gene order for the region of the ribonucleic acid coding for the capsid proteins as (5′ → 3′) VP 4 - VP 2 - VP 3 - VP 1.